2021
DOI: 10.1136/bcr-2021-242678
|View full text |Cite
|
Sign up to set email alerts
|

Immune thrombocytopenic purpura and acute liver injury after COVID-19 vaccine

Abstract: A 26-year-old woman was sent to the emergency room by her primary care physician for a new petechial rash and thrombocytopenia 2 weeks after receiving the Moderna mRNA-1273 SARS-CoV-2 vaccine. Her hospital course was complicated by transaminitis. Her platelet count improved to normal on hospital day 5 after receiving intravenous steroids and intravenous immunoglobulin to treat her suspected diagnosis of immune thrombocytopenic purpura. Extensive workup for her thrombocytopenia and transaminitis was unremarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 4 publications
(4 reference statements)
0
25
0
Order By: Relevance
“…Cases of ITP and TTP after mRNA-1273 COVID-19 vaccine have been documented since the early vaccination campaign (165)(166)(167)(168). A flare of familial thrombocytopenia has been r e p o r t e d a s w e l l ( 1 6 9 ) .…”
Section: Mrna-1273 (Moderna) and Vitt7vipittmentioning
confidence: 99%
“…Cases of ITP and TTP after mRNA-1273 COVID-19 vaccine have been documented since the early vaccination campaign (165)(166)(167)(168). A flare of familial thrombocytopenia has been r e p o r t e d a s w e l l ( 1 6 9 ) .…”
Section: Mrna-1273 (Moderna) and Vitt7vipittmentioning
confidence: 99%
“…Mild side effects, which are the most common, include swelling at injection site, fever and myalgia. However, more serious side effects such as seizure, life-threatening allergic reactions and thrombocytopenia have been reported as well [2] , [4] . Some trials also reported decreased hemoglobin, increased bilirubin, elevated AST (aspartate aminotransferase) and ALT (alanine aminotransferase) [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Hematological events such as ITP has already been related to the use of vaccines, specifically live attenuated vaccines such as measles, mumps and rubella [4] . The onset of vaccine-related ITP usually has a time relationship, occurring mainly within 42 days after vaccination [5] . Since the beginning of the COVID-19 mass immunization campaign, several case-reports or case-series of ITP following vaccination have been described in the literature [5] , [6] , [7] , [8] .…”
Section: Discussionmentioning
confidence: 99%
“…The onset of vaccine-related ITP usually has a time relationship, occurring mainly within 42 days after vaccination [5] . Since the beginning of the COVID-19 mass immunization campaign, several case-reports or case-series of ITP following vaccination have been described in the literature [5] , [6] , [7] , [8] . In some cases, underlying autoimmune medical conditions may have contributed to the ITP occurrence but it appears infrequent [8] .…”
Section: Discussionmentioning
confidence: 99%